Direct Prediction of EPR Spectra from Lipid Bilayers: Understanding Structure and Dynamics in Biological Membranes. Issue 17 (19th June 2018) - Catte, Andrea; White, Gaye F.; Wilson, Mark R.; Oganesyan, Vasily S.
Abstract: Of the many biophysical techniques now being brought to bear on studies of membranes, electron paramagnetic resonance (EPR) of nitroxide spin probes was the first to provide information about both mobility and ordering in lipid membranes. Here, we report the first prediction of variable temperature EPR spectra of model lipid bilayers in the presence and absence of cholesterol from the results of large scale fully atomistic molecular dynamics (MD) simulations. Three types of structurally different spin probes were employed in order to study different parts of the bilayer. Our results demonstrate very good agreement with experiment and thus confirm the accuracy of the latest lipid force fields. The atomic resolution of the simulations allows the interpretation of the molecular motions and interactions in terms of their impact on the sensitive EPR line shapes. Direct versus indirect effects of cholesterol on the dynamics of spin probes are analysed. Given the complexity of structural organisation in lipid bilayers, the advantage of using a combined MD‐EPR simulation approach is two‐fold. Firstly, prediction of EPR line shapes directly from MD trajectories of actual phospholipid structures allows unambiguous interpretation of EPR spectra of biological membranes in terms of complex motions. Secondly, such an approach provides an ultimate test bed for the up‐to‐date MD simulation models employed in the studies of biological membranes, an area that currently attracts great attention. Abstract : Put a spin on it ! Prediction of variable temperature EPR spectra from large scale all‐atom MD simulations of lipid bilayers doped with spin probes provides a direct interpretation of EPR line shapes from actual molecular motions and serves as a rigorous test bed for MD models employed in the studies of biological membranes.